2019
DOI: 10.1186/s12879-019-4228-4
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific real-time PCR testing for minor macrolide-resistant Mycoplasma Pneumoniae

Abstract: Background The point mutations in 23S rRNA gene of Mycoplasma pneumoniae ( M. pneumoniae ) can lead to high-level resistance to macrolides. This study aimed to evaluate allele-specific real-time PCR (ASPCR) to detect the resistance-related mutations located at positions A2063G and A2064G of 23S rRNA gene. Methods We detected 178 pharyngeal swab specimens and calculated the proportions of resistant and sensitive quasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
12
2
Order By: Relevance
“…The mutation rate in this study was 56.07%, of which were all A2063G mutations. The rate of drug-resistant MP was lower than those reported in other studies in China, where the rates range from almost 70-90% [20][21][22] . This is the because point mutations in drug-resistance genes were detected by PCR in this study, while drug sensitivity tests were chosen by other researchers.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The mutation rate in this study was 56.07%, of which were all A2063G mutations. The rate of drug-resistant MP was lower than those reported in other studies in China, where the rates range from almost 70-90% [20][21][22] . This is the because point mutations in drug-resistance genes were detected by PCR in this study, while drug sensitivity tests were chosen by other researchers.…”
Section: Discussioncontrasting
confidence: 72%
“…1). ADV infection may cause severe disease necessitating ICU admission and mechanical ventilation [20] .…”
Section: Discussionmentioning
confidence: 99%
“…The mutation rate in this study was 56.07%, of which were all A2063G mutations. The rate of drug-resistant MP was lower than those reported in other studies in China, where the rates range from almost 70 to 90% [21,22,24]. This is the because point mutations in drug-resistance genes were detected by PCR in this study, while drug sensitivity tests were chosen by other researchers.…”
Section: Discussionmentioning
confidence: 57%
“…However, in this study, no remarkable differences in clinical characteristics were observed between patients who were and were not coinfected, except for in those with ADV coinfections. ADV infection may cause severe disease necessitating ICU admission and mechanical ventilation [21]. The severity of pneumonia with ADV coinfection is significantly related to viral load and serotypes, and children with ADV genotype 7 develop severe pneumonia more frequently than those with other genotypes [22].…”
Section: Discussionmentioning
confidence: 99%
“…ADV infection may cause severe disease necessitating ICU admission and mechanical ventilation [21] .…”
Section: Discussionmentioning
confidence: 99%